INTEGRATION OF THE FERMENTATION OF ORGANIC SOLID WASTE - Erazo Erazo, R. (2004)
It has been developed a process of integration of fermentation systems of organical solid waste (OSW) in facilities of the «La Vizcacha» filling field, Puente Piedra District-Lima. We are obtained 225 mL ethanol and 0,008 5 kWh per kilogramm of urban solid waste.